Mabuhay! - Sterling, Zack (Graphix, an imprint of Scholastic, 2023)
"First-generation Filipino siblings, JJ and Althea, struggle to belong at school. JJ wants to fit in with the crowd, while Althea wants to be accepted as she is. But between the leftover Filipino food their mom packs for their lunches to having a last name that nobody can pronounce, any sense of belonging seems like a long shot. To make matters worse, they have to help their parents run the family food truck, dressing up as a dancing pig and passing out samples. Ugh! And their parents are always drawing parallels between their poor work ethic and lazy characters from Filipino folklore -- stories they've heard again and again. But when witches, ogres, and other creatures from those same stories appear in their town and threaten their family, JJ and Althea realize that the myths their parents have always told them may be more real than they'd suspected. Can JJ and Althea embrace who they really are and save their family?"--